Perbandingan Model Promosi pada Platform Facebook, Instagram, dan Tiktok terhadap Keputusan Pembelian berdasarkan model AISAS - Aulia, Hafizah; Mu'arrif, Zul Ihsan; Sumanti, Eva (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the comparison of promotional models on social media on generation Z purchasing decisions in Sungai Full based on the AISAS (Attention, Interest, Search, Action and Share) marketing communication model. In this study, data was collected through the questionnaire method. The population of this study was Generation Z in Sungai Penuh (11-25 years), and the sample used was 90 people. Data analysis in this study used Smart PLS 3.0. The results of this research show that Instagram is the social media that is widely used by generation Z in Sungai Penuh namely 72.2%, 62.2% of TikTok users, and only 26.7% of Facebook, and promotions using the AISAS (Attention, Interest) model. , search, action and share) on social media Facebook do not have a significant effect on purchasing decisions in generation Z in Sungai Penuh. On social media Instagram it is known that interest, search and share have a significant effect on purchasing decisions in generation Z in Sungai Penuh, while attention and action does not have a significant effect on purchasing decisions in Generation Z in Sungai Penuh, on Tiktok social media, attention, interest and share have a significant effect on purchasing decisions in Generation Z in Sungai Penuh, while search and action do not have a significant effect on purchasing decisions in Generation Z in Sungai Penuh.